The Czech Republic and the 2022 and 2023 Reintroduction of Border Controls: Framing Secondary Movements as a Threat to National Security in the Regional Context - Věra Honusková; Enes Zaimović (European Papers)
(Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1250-1267 | Article | (Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1250-1267 | Article | (Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1250-1267 | Article | (Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1250-1267 | Article | (Series Information) European Papers - A Journal on Law and Integration, 2024 9(3), 1250-1266 | Article | (Table of Contents) I. Introduction. – II. Reintroduction of Internal Border Controls in the Czech Republic in 2022 and 2023. – III. Czech reintroduction of border controls in light of relevant EU law. – IV. Sovereignty as a (mis)used and forgotten argument. – V. Conclusion and the way forward. | (Abstract) Since 2015, Western and Central European member states along the Balkan route have repeatedly responded to the increased number of arriving migrants by reintroducing internal border controls. They did so deliberately and at the cost of sacrificing one of the major achievements of the European integration process: the principle of free movement and the area without internal frontiers. The presented Article focuses on legal assessment of these responses. Using the example of the Czech reintroduction of border controls on the land border with Slovakia in 2022/23 and 2023/24, we demonstrate how legal responses of member states may intertwine with domestic politics and how states take a somewhat hesitant approach to law in the face of migratory pressure. The Czech example also illustrates how states, despite their international and EU obligations, adopt specific measures without properly considering adequate and more proportionate alternatives.